Use of Special Exams for More Precise Diagnosis of Corneal Ectasia. Case Report - Vidal Olarte, Rosario (Universidad de La Salle. Revistas. Ciencia y Tecnología para la Salud Visual y Ocular., 2013)
Visual and ocular health professionals are currently faced with the typical cases of primary and secondary corneal ectasia, and even though the most frequent ones are keratoconus, it is not always so. Hence the importance of a good clinical correlation, as well as of the request of special tests in order to help achieve a better diagnosis. It is essential to remember that, in most cases, they are asymmetric binocular processes, so that if one eye presents more advanced symptoms, the opposite eye should also be monitored, because the condition will most likely develop further. The case of a sixteen year old Computer Technology student diagnosed with keratoconus is presented.